Teaching portfolio system based on application / 'Ainaa Abdul Rashid - Abdul Rashid, 'Ainaa (2005)
A teaching portfolio is a coherent set of material that represents the teaching practice as related to student learning. The primary objective of teaching portfolio is educative and designed to meet program objective. The main objective of this research project is to create an electronic teaching portfolio platform for lecturers in FTMSK by using JAVA application as the existing system is manually done. This project was written using RealJ program. In this research project paper, there were specific steps to ensure the completion of the research. The first step was done to identity user requirements and specifications. Second step was to identify the activities that had to be included in the electronic teaching portfolio such as course information, scheme of work, attendance and assessment. The next step was committed to collect data and information from related sources and the fourth step was to design and implement the application. Programming and data acquisition were done by programmer in the fifth step. Finally, the report writing and user documentation were prepared as a reference in the future. System limitation and recommendations for further improvement were discussed in the conclusion chapter. As a conclusion, this system is a compliment for the manual existing teaching portfolio system and not the replacement for the existing one.